Point‐of‐care testing in haemostasis - Perry, David J.; Fitzmaurice, David A.; Kitchen, Steve; Mackie, Ian J.; Mallett, Sue (British journal of haematology, 2010)
Summary Point‐of‐care testing (POCT) in haematology has seen a significant increase in both the spectrum of tests available and the number of tests performed annually. POCT is frequently undertaken with the belief that this will reduce the turnaround time for results and so improve patient care. The most obvious example of POCT in haemostasis is the out‐of‐hospital monitoring of the International Normalized Ratio in patients receiving a vitamin K antagonist, such as warfarin. Other areas include the use of the Activated Clotting Time to monitor anticoagulation for patients on cardio‐pulmonary bypass, platelet function testing to identify patients with apparent aspirin or clopidogrel resistance and thrombelastography to guide blood product replacement during cardiac and hepatic surgery. In contrast to laboratory testing, POCT is frequently undertaken by untrained or semi‐trained individuals and in many cases is not subject to the same strict quality control programmes that exist in the central laboratory. Although external quality assessment programmes do exist for some POCT assays these are still relatively few. The use of POCT in haematology, particularly in the field of haemostasis, is likely to expand and it is important that systems are in place to ensure that the generated results are accurate and precise.